Red Blood Cell and Endothelial eNOS Independently Regulate Circulating Nitric Oxide Metabolites and Blood Pressure. Issue 11 (7th July 2021) - Leo, Francesca; Suvorava, Tatsiana; Heuser, Sophia K.; Li, Junjie; LoBue, Anthea; Barbarino, Frederik; Piragine, Eugenia; Schneckmann, Rebekka; Hutzler, Beate; Good, Miranda E.; Fernandez, Bernadette O.; Vornholz, Lukas; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Current paradigms suggest that nitric oxide (NO) produced by endothelial cells (ECs) through endothelial nitric oxide synthase (eNOS) in the vessel wall is the primary regulator of blood flow and blood pressure. However, red blood cells (RBCs) also carry a catalytically active eNOS, but its role is controversial and remains undefined. This study aimed to elucidate the functional significance of RBC eNOS compared with EC eNOS for vascular hemodynamics and nitric oxide metabolism. Methods: We generated tissue-specific loss- and gain-of-function models for eNOS by using cell-specific Cre-induced gene inactivation or reactivation. We created 2 founder lines carrying a floxed eNOS (eNOS flox/flox ) for Cre-inducible knockout (KO), and gene construct with an inactivated floxed/inverted exon (eNOS inv/inv ) for a Cre-inducible knock-in (KI), which respectively allow targeted deletion or reactivation of eNOS in erythroid cells (RBC eNOS KO or RBC eNOS KI mice) or in ECs (EC eNOS KO or EC eNOS KI mice). Vascular function, hemodynamics, and nitric oxide metabolism were compared ex vivo and in vivo. Results: The EC eNOS KOs exhibited significantly impaired aortic dilatory responses to acetylcholine, loss of flow-mediated dilation, and increased systolic and diastolic blood pressure. RBC eNOS KO mice showed no alterations in acetylcholine-mediated dilation or flow-mediated dilation but were hypertensive. Treatment with the nitric oxide synthase inhibitor N γ -nitro-l -arginine methyl ester further increased blood pressure in RBC eNOS KOs, demonstrating that eNOS in both ECs and RBCs contributes to blood pressure regulation. Although both EC eNOS KOs and RBC eNOS KOs had lower plasma nitrite and nitrate concentrations, the levels of bound NO in RBCs were lower in RBC eNOS KOs than in EC eNOS KOs. Reactivation of eNOS in ECs or RBCs rescues the hypertensive phenotype of the eNOS inv/inv mice, whereas the levels of bound NO were restored only in RBC eNOS KI mice. Conclusions: These data reveal that eNOS in ECs and RBCs contribute independently to blood pressure homeostasis.